AVAREG: a phase II, randomized, noncomparative study of fotemustine or bevacizumab for patients with recurrent glioblastoma. Issue 9 (1st September 2016) - Brandes, Alba A.; Finocchiaro, Gaetano; Zagonel, Vittorina; Reni, Michele; Caserta, Claudia; Fabi, Alessandra; Clavarezza, Matteo; Maiello, Evaristo; Eoli, Marica; Lombardi, Giuseppe; Monteforte, Marta; Proietti, Emanuela; et al.
Abstract: Background: Few prospective studies have assessed the role of bevacizumab and included a control arm with standard treatments for recurrent glioblastoma. We conducted a noncomparative phase II trial (AVAREG) to examine the efficacy of bevacizumab or fotemustine in this setting. Methods: Eligible patients were randomized 2:1 to receive bevacizumab (10 mg/kg every 2 weeks) or fotemustine (75 mg/m 2 on days 1, 8, and 15, then 100 mg/m 2 every 3 weeks after a 35-day interval). The primary endpoint was 6-month overall survival (OS) rate (OS-6). No formal efficacy comparison was made between the treatment arms. Results: Ninety-one patients were enrolled (bevacizumab n = 59; fotemustine n = 32). Median age was 57 years (range, 28–78 y), and patients had Eastern Cooperative Oncology Group performance status of 0 ( n = 42), 1 ( n = 35), or 2 ( n = 14). OS-6 rate was 62.1% (95% confidence interval [CI], 48.4–74.5) with bevacizumab and 73.3% (95% CI, 54.1–87.7) with fotemustine. OS-6 rates were lower in bevacizumab-treated patients with MGMT promoter methylated tumors than in those with unmethylated tumors (50% and 85%, respectively), but higher in fotemustine-treated patients (87.5% and 50%, respectively). OS rates at 9 months were 37.9% (95% CI, 25.5–51.6) and 46.7% (95% CI, 28.3–65.7) with bevacizumab and fotemustine, respectively, and median OS was 7.3 months (95% CI, 5.8–9.2) and 8.7 months (95% CI, 6.3–15.4), respectively. Toxicity was as expected with the 2 agents. Conclusion: Single-agent bevacizumab may have a role in patients with recurrent glioblastoma.